2015
DOI: 10.1007/s10140-015-1305-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical scoring system may improve yield of head CT of non-trauma emergency department patients

Abstract: Purpose The positive rate of head CT in non-trauma patients presenting to the Emergency Department (ED) is low. Currently, indications for imaging are based on the individual experience of the treating physician, which contributes to overutilization and variability in imaging utilization. The goals of this study are to ascertain the predictors of positive head CT in non-trauma patients and demonstrate feasibility of a clinical scoring algorithm to improve yield. Methods We retrospectively reviewed 500 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 10 publications
7
48
2
1
Order By: Relevance
“…As an example, studies of positive rates of non-trauma head CTs found abnormalities ranging from 10% to 39%; trauma head CT rates were ~29%. [20][21][22] For non-trauma and trauma head scans, abnormal findings in this study were 53.8% and 45.1%, respectively, which were also higher than most. A study done in Malaysia reported a positive rate of 70.5%.…”
Section: Researchmentioning
confidence: 84%
“…As an example, studies of positive rates of non-trauma head CTs found abnormalities ranging from 10% to 39%; trauma head CT rates were ~29%. [20][21][22] For non-trauma and trauma head scans, abnormal findings in this study were 53.8% and 45.1%, respectively, which were also higher than most. A study done in Malaysia reported a positive rate of 70.5%.…”
Section: Researchmentioning
confidence: 84%
“…Some have advocated for specific clinical decision rules for determining who should receive neuroimaging for acute headache, especially when the differential includes subarachnoid hemorrhage [7]. Others have suggested using clinical risk factors to stratify patients' overall risk for actionable CT results [8] or using online clinical decision support tools to ensure that only those patients who meet certain criteria will receive appropriate use of resources [9]. While CT assessment is an important tool in assessing cranial pathology in the emergency department (ED), appropriateness criteria should be utilized to ensure that the potential benefits outweigh the harms [10].…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, the CDRs proposed in the past for NTBI have received little attention and validation. These criteria include those by Rothrock et al , Harris et al , Wang and You and Bent et al (Table ). In particular, the Rothrock and Harris criteria have both been validated previously, and their initial, high sensitivities and scan reduction rates have not been reproducible …”
Section: Introductionmentioning
confidence: 99%
“…The data were clearly defined and were either categorical, such as headache (yes or no), or continuous, such as heart rate or temperature. Coagulopathy was defined as thrombocytopenia, clotting factor variant or deficiency or bleeding disorders such as haemophilia or disseminated intravascular coagulopathy . The researchers were not blinded to the study objective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation